Clinical dose effect and functional consequences of R92Q in two families presenting with a TRAPS/PFAPA‐like phenotype. Issue 2 (14th January 2017) - Grandemange, Sylvie; Cabasson, Sébastien; Sarrabay, Guillaume; Pène, Jérôme; Rittore, Cécile; Sanchez, Elodie; Chastang, Marie‐Caroline; Guyon, Gaël; Pillet, Pascal; Touitou, Isabelle
Abstract: Background: TNF receptor‐associated syndrome (TRAPS) is a dominantly inherited autoinflammatory condition caused by mutations in the TNFRSF1A gene. The mechanism underlying the variable expressivity of the common variant R92Q (rs4149584 ; c.362G>A; p.Arg121Gln) is unclear and is of critical importance for patient care and genetic counseling. This study evaluated the impact of the number of R92Q mutations in two unique unrelated families. Methods: Two patients with undefined but clear autoinflammatory symptoms were referred for genetic diagnosis. Blood samples were collected from the available family members to screen autoinflammatory genes and assess key steps of the TNFR1‐mediated signaling pathway using flow cytometry and ex vivo culture. Results: R92Q homozygosity was demonstrated for the two probands. In family 1, the segregation analysis revealed TRAPS‐like symptoms in all carriers, with a more severe presentation in the proband, whereas in family 2, the heterozygous parents were totally asymptomatic, suggesting recessive transmission. Functional studies revealed a nonclassical pathogenesis of TRAPS in the two probands and suggested a compensatory mechanism without clear dose effect. Conclusion: We observed for the first time a possible clinical dose effect of R92Q. This work highlights the importance of familial studies to reconcile the contradictory reports published on the pathogenicity of this variant. Abstract : We describe two probands presenting with a TRAPS‐like phenotype. TNFRSF1A screening revealed R92Q homozygosity for both, a clinical dose effect in family 1 and a possible recessive transmission of R92Q in family 2. Functional studies revealed a nonclassical pathogenesis of TRAPS in the two probands and suggested a compensatory mechanism. This study provides the first familial investigation of the impact of the number of R92Q variants at both clinical and functional levels.